2015
DOI: 10.1007/978-3-0348-0927-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Celery Seed and Related Extracts with Antiarthritic, Antiulcer, and Antimicrobial Activities

Abstract: Celery preparations have been used extensively for several millennia as natural therapies for acute and chronic painful or inflammatory conditions. This chapter reviews some of the biological and chemical properties of various celery preparations that have been used as natural remedies. Many of these have varying activities and product qualities. A fully standardized celery preparation has been prepared known as an alcoholic extract of the seeds of a plant source derived from northern India. This is termed, Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…It proves that AG is potential as an herbal remedy. The antioxidants insides the AG are utilised as the antiparasite (Kumar et al, 2014), antitumour (Danciu et al, 2018) and antibacterial agents (Powanda et al, 2015). The other herb is SA which contains several active constituents such as glycoside, flavonoid, and alkaloid that potential as the antitoxic and antioxidant (Prabhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It proves that AG is potential as an herbal remedy. The antioxidants insides the AG are utilised as the antiparasite (Kumar et al, 2014), antitumour (Danciu et al, 2018) and antibacterial agents (Powanda et al, 2015). The other herb is SA which contains several active constituents such as glycoside, flavonoid, and alkaloid that potential as the antitoxic and antioxidant (Prabhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the extract has been shown to inhibit the proliferation and migration of MCF7 breast cancer cell line [ 19 ]. Celery seeds extracts have been described for their antioxidant, antimicrobial, antiarthritic, and antiulcer potential [ 20 , 21 ]. The group of Mansi et al have also found that the extract can induce a hypolipidemic effect in rats [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[32] Similarly, Swertiamarin attenuates inflammation mediators via modulating NFκB/IkB and JAK STAT3 transcription factors in adjuvantinduced arthritis, [33] Celery seeds also show anti-arthritic activity. [34] Tinospora cordifolia, [35] Terminalia chebula Retz, [36] and Ajuga bracteosa Wall ex Benth [37] and Lakshadi Guggul showed strong anti-arthritic potential in albino rats [ Table 1]. [38] A regular treatment significantly reduces both the arthritic index (AI) and the CIA incidence.…”
Section: Nutraceuticalsmentioning
confidence: 99%